Rola banków w finansowaniu przedsiębiorstw - doświadczenia polskie na tle rozwiązań europejskich - Franek, Sławomir (Banks in Corporate Finance - Polish and European Experiences, 2007)
This article analyses the development of the use of external sources of corporate finance in Poland and UE, especially in the context of the use of banking financing. The main subject of the research is the influence of credit spreads and the stance of economy on the financial decisions in corporations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 166-174